Fault-tolerant control of six-phase induction motor drives with variable current injection - González Prieto, Ignacio; Durán-Martínez, Mario Javier; Barrero, Federico (IEEE, 2016)
Three-phase machines are the industry standard for electrical drives, but the inherent fault tolerance of multiphase machines makes them an attractive alternative in applications requiring high reliability. For this reason, different fault-tolerant control schemes for multiphase drives have been recently suggested, proving their capability to perform a ripple-free operation after an open-circuit fault occurrence. Nevertheless, the postfault strategies proposed so far consider a single mode of operation and do not allow a high-performance braking process in drives with unidirectional power flow where regenerative braking is not possible. This paper first explores the possibility of enhancing the braking process by using a proper injection of circulating currents that prevent the active power to reach the dc-link capacitor. This novel strategy is then combined with minimum losses and maximum torque criteria to obtain a variable current injection method that minimizes the drive derating, reduces the copper losses, and improves the braking transients. Experimental results confirm the successful performance in the different zones for the case of a six-phase induction motor drive.
Keywords: Motores de inducción; Tolerancia a los fallos (Informática); Braking methods; Fault tolerance; Induction motors; Multiphase drives; Open-circuit faults